ESTIMATING POROSITY AND WATER SATURATION FROM SEISMIC/ACOUSTIC SIGNALS: A CORRECTION ON THE EFFECT OF SHALINESS - Bambang Widarsono; Fakhriyadi Saptono (Scientific Contributions Oil and Gas, 2000)
The presence of shale in sedimentary rocks tends to introduce complexity in any formation evaluation activities. This is also the case when efforts are spent in estabilishing a method that enables analysts to estimate porosity and water saturation from seismic survey.